(3SjQI GdSdWGf GdTgjO Gdedc GdXGgQ Lbebs - (3CMeO Hf eMeO Hf YHO Gddg Hf EHQGgje, CHh eMeO, TgGH GdOjf, GdeYQha HGHf nYnQrHTGg , J (B854 (3g` s
(3ChdgG (B:s
(3hCNQi JMHhfgG fUQ ef Gddg haJM bQjH s
(3fSNI NRGFfjI ocJHJ HQSe EjfGd GdCTbQ Gdedci GdXGgQjIs
(3Vefg SjQI Gdedc GdXGgQ CHj SYjOLbeb GdPj Jhdi edc eUQ (B482-985(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B122s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B29 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B87 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs